Analisis Pengaruh Aglomerasi Industri, Jumlah Penduduk terhadap Tingkat Disparitas Pendapatan di Sumbagsel dalam Perspektif Ekonomi Islam : Analisis Data Panel Tahun 2015-2024 - Innez Dara Puspita; Asriani Asriani; Yulistia Devi (Institut Teknologi dan Bisnis (ITB) Semarang, 2025)
The issue of income disparity among regions in the Southern Sumatra (Sumbagsel) area remains a relevant challenge in regional economic development. Regions with high industrial concentration and large populations do not necessarily exhibit equitable income distribution. This study aims to analyze the effect of industrial agglomeration and population size on income disparity in the Sumbagsel region during the 2015–2024 period, both partially and simultaneously, and to interpret the findings within the framework of Islamic economics. This research employs a quantitative approach with panel data analysis. The secondary data cover five provinces in the Sumbagsel region—South Sumatra, Lampung, Jambi, Bangka Belitung, and Bengkulu—over the period of 2015–2024. The data were analyzed using panel data regression with the Fixed Effect Model (FEM) approach through the EViews 10 software. The independent variables are industrial agglomeration and population size, while the dependent variable is income disparity. The findings reveal that, partially, industrial agglomeration has a negative and significant effect on income disparity, while population size has a negative but insignificant effect. Simultaneously, both variables have a significant influence on income disparity in the Sumbagsel region. From the Islamic economic perspective, these results align with the principles of maqasid syari’ah, particularly in preserving wealth (hifz al-mal) and promoting public welfare (maslahah ‘ammah).